Evaluation of 11kv XLPE Cable - Bashir Umar, Nouruddeen (2006)
Underground power cables constitute a bulk part of power systems network. Most of these power system equipments have been in service for decades, thus making their insulation liable to deterioration (ageing) as a result of operational and environmental stresses. For the past decades, the Recovery Voltage Method (RVM) has been widely used to evaluate ageing in oil-paper insulated cables. This work presents the evaluation of ageing in 11kV XLPE cable using the RVM. Statistical Analysis was employed to predict the progress of ageing. Accelerated ageing using AC and impulse voltages was performed on new XLPE cable samples. Within the period of ageing, the state of insulation was investigated and assessed using the RVM. Regression Analysis was used to predict the progress of ageing in cables, with the CTC (central time constant) being the response variable. However due to technical problems encountered in the course of this study, synthetic data were used to model the regression equation. The result of the diagnosis using the RVM showed that the aged XLPE cables had higher values of Urmax (maximum return voltage) than the unaged ones, indicating the samples have undergone thermal ageing. An R2 of 0.981 was obtained from the regression equation, implying that the predicted values of the CTC were 98.1% close to the observed values. The RVM technique, which was initially proposed for diagnosis of oil-paper insulation systems, was found to be able to detect ageing in XLPE cables, and thus insulation diagnosis using this technique could be extended to extruded-insulated cable systems. The Regression Analysis, a tool for forecasting and prediction, can be used to predict the progress of insulation deterioration and ageing